(untitled) (Alternautas, 2022)
Youth indigenous activism, territorial struggles, decoloniality, Colombia April 9th 2012 was the day that, in the Sociology Department of the National University of Colombia in Bogotá, the thoughts and feelings of five young people started to grow into something bigger. As sons and daughters of the large Natagaimas and Coyaimas territories we came together to name our nascent group as Grupo Pijao. This group is a seed that we continue to sow and harvest today in our territories through different strategies.